Promotive and preventive education of non-communicable diseases for the community - Daniel Suranta Ginting; Muh Ihsan Kamaruddin; Anita Lontaan (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2024)
Non-communicable diseases such as diabetes, cancer, and heart disease are global health challenges that require a holistic approach to their prevention and management. Promotive and preventive education has been recognized as an effective strategy for increasing public health awareness and reducing the incidence of non-communicable diseases. This service activity can improve health awareness in the community, primarily related to promotive and preventive education. Measures such as education campaigns, education in schools, collaboration with communities, and the use of technology have been discussed as effective strategies for achieving this goal. In conclusion, the joint efforts of different parties and diverse methods are crucial to creating an environment that supports high health awareness. Implementing the right strategy is expected to increase public understanding of the importance of a healthy lifestyle and the prevention of non-communicable diseases and produce positive behavioral change in the long term. Joint efforts from different sectors and diverse methods can help increase health awareness in the community, realize a healthy lifestyle, and reduce the risk of non-communicable diseases significantly. Health awareness includes an understanding of a healthy lifestyle and the ability to implement that knowledge in everyday life.